Positive teacher–student relationships go beyond the classroom, problematic ones stay inside. Issue 5 (3rd September 2017) - Claessens, Luce C. A.; van Tartwijk, Jan; van der Want, Anna C.; Pennings, Helena J. M.; Verloop, Nico; den Brok, Perry J.; Wubbels, Theo
ABSTRACT: The authors voice teachers' perceptions of their interpersonal experiences with students in both positive and problematic relationships. Interview data from 28 teachers were examined by coding utterances on teacher and student interactions. Results indicate that teachers defined the quality of the relationship mostly by the level of communion (friendly vs. hostile), instead of by the level of agency (in control vs. powerless). Analyses of mentioned teacher and student behavior show a friendly interactional pattern for positive relationships and a hostile pattern for problematic ones. In teachers' perceptions, positive and problematic relationships also differed in context where encounters take place and topic of talk. Contrary to interactions in problematic relationships, encounters in positive relationships were mostly situated outside the classroom context and conversations during these encounters covered a wide range of topics. Implications for teacher education programs are discussed.